The First Chemistry Department in Port Elizabeth - Loyson, Peter (African Sun Media, 2017)
The first Chemistry Department in Port Elizabeth was founded in 1929 at the PE Technical College in Russell Road. This institution was later renamed the College for Advanced Technical Education (CATE) and still later it became the PE Technikon, when it moved to its Summerstrand Campus. This is the story of this Chemistry Department over 75 years, until 2005, when the Technikon became part of the newly established Nelson Mandela Metropolitan University. Archive material was used to compile the story of the various Heads of Department and their staff, who contributed so much in making this Department so successful.